(Dis)Parallel Encounters: School and Life Paths of Young People in Vulnerable Situations (Revista Lusófona de Educação, 2025)
Portuguese education policies have been guided by indicators of social justice, such as equity and inclusion, recognition of diversity, learning opportunities, and the distribution of resources. Although there appears to be a broad consensus regarding the relevance of these guidelines, implementation challenges persist, particularly in relation to the (dis)connections within the school trajectories of young people in situations of greater social vulnerability. Based on these premises, the article presents a study whose main objectives were to characterise and understand the school trajectories of young people marked by absenteeism, dropout, and resistance. The research adopted a qualitative approach, using interviews with 21 young people experiencing school fragmentation and transitioning to other socio-educational contexts, seeking a late reconstruction of meaning in relation to school life. Data were analysed using thematic analysis in order to identify recurring patterns and themes in the young people’s narratives. The findings show that many have faced resistance and exclusion since childhood, living in contexts of familial, economic, and social vulnerability, and expressing disillusionment and mistrust towards school and the educational system. This is evident in the cycles of school leaving and return, and the resulting tendency towards marginalisation and dropout.Keywords: Young people; Early school leaving; Exclusion and resistance; Citizenship and social justice